Peran Tuha Peut Dalam Perencanaan Pemberdayaan Masyarakat Gampong Ujong Drien - Yolanda, Selfia; Saadah, Nailis; Fitri, Susila; Putra, Nirja; Sopar (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Gampong is the lowest level of government in the government system in Indonesia. In recent years, gampong or villages have been given great authority in carrying out village governance, especially in managing community empowerment in Gampong Ujong Drien. Tuha Peut is given authority in carrying out supervisory functions, especially supervising the performance of the village government. The formulation of the problem in this study is limited to the Role of Tuha Peut in Planning Community Empowerment in Gampong Ujong Drien. This study includes qualitative research as a process to provide a complex understanding of what happens in community empowerment.